P.K. Pinkerton and the pistol-packing widows - Lawrence, Caroline (New York, NY : G.P. Putnam's Sons, an imprint of Penguin Group (USA) Inc., 2014)
In 1860s Nevada, master-of-disguise P.K. Pinkerton uncovers a sinister plot when he takes a case that calls for him to shadow his friend and mentor, Poker Face Jace.
Keywords: Detective and mystery stories; Disguise -- Juvenile fiction; Orphans -- Juvenile fiction; Multiracial people -- Juvenile fiction; Nevada -- History -- 19th century -- Juvenile fiction; Mystery and detective stories; Disguise -- Fiction; Orphans -- Fiction; Multiracial people -- Fiction; Nevada -- History -- 19th century -- Fiction